Open in App
Not now

# Class 9 RD Sharma Solutions – Chapter 13 Linear Equation in Two Variable- Exercise 13.2

• Last Updated : 11 Dec, 2020

### Question 1. Write two solutions for each of the following equations:(i) 3x + 4y = 7(ii) x = 6y(iii) x + Ï€y = 4(iv) 2/3 x âˆ’ y = 4

Solution:

(i) 3x + 4y = 7
Substituting x =1
We get,
3Ã—1 + 4y = 7
4y = 7 âˆ’ 3
4y = 4
y = 1
Therefore, if x = 1, then y =1, is the solution of 3x + 4y = 7

Substituting x = 2
We get,
3Ã—2 + 4y = 7
6 + 4y = 7
4y = 7 âˆ’ 6
y =
4
Therefore, if x = 2, then y =  1 , is the solution of 3x + 4y = 7
4

(ii) x = 6y
Substituting x =0
We get,
6y = 0
y = 0
Therefore, if x = 0, then y =0, is the solution of x = 6y

Substituting x = 6
We get,
6 = 6y
y =
6
y = 1
Therefore, if x = 6, then y =1, is the solution of x = 6y

(iii) x + Ï€y = 4
Substituting x = 0
We get,
Ï€y = 4
y =
Ï€
Therefore, if x = 0, then y =  is the solution of x + Ï€y = 4
Ï€

Substituting y =0
We get,
x + 0 = 4
x = 4
Therefore, if y = 0, then x = 4 is the solution of x + Ï€y = 4

(iv) 2 x âˆ’ y = 4
3
Substituting x = 0
We get,
0 âˆ’ y = 4
y = âˆ’4
Therefore, if x = 0, then y = âˆ’4 is the solution of  x âˆ’ y = 4
3
Substituting x =3
We get,
2 Ã—3 âˆ’ y = 4
3
2 âˆ’ y = 4
y = 4 âˆ’ 2
y = âˆ’2
Therefore, if x = 3, then y = âˆ’2 is the solution of  2 x âˆ’ y = 4
3

### Question 2. Write two solutions of the form x = 0, y =a and x = b, y = 0 for each of the following equations:(i) 5x âˆ’ 2y = 10(ii) âˆ’4x + 3y = 12(iii) 2x + 3y = 24

Solution:

(i) 5x âˆ’ 2y = 10
Substituting x =0
We get,
5Ã—0 âˆ’ 2y = 10
âˆ’2y = 10
âˆ’y =  10
2
y = âˆ’5
Therefore, if x = 0, then y = âˆ’5 is the solution of 5x âˆ’ 2y = 10

Substituting y = 0
We get,
5x âˆ’ 2Ã—0 = 10
5x = 10
x =  10
5
x = 2
Therefore, if y = 0, then x = 2 is the solution of 5x âˆ’ 2y = 10

(ii) âˆ’4x + 3y = 12
Substituting x = 0
We get,
âˆ’4Ã—0 + 3y = 12
3y = 12
y =  12
3
y = 4
Therefore, if x = 0, then y = 4 is the solution of âˆ’4x + 3y = 12

Substituting y = 0
âˆ’4x + 3 x 0 = 12
â€“ 4x = 12
x = âˆ’3
Therefore, if y = 0 then x = âˆ’3 is a solution of âˆ’4x + 3y = 12

(iii) 2x + 3y = 24
Substituting x = 0
2Ã—0 + 3y = 24
3y =24
y = 8
Therefore, if x = 0 then y = 8 is a solution of 2x+ 3y = 24

Substituting y = 0
2x + 3Ã—0 = 24
2x = 24
x =12
Therefore, if y = 0 then x = 12 is a solution of 2x + 3y = 24

### Question 3. Check which of the following are solutions of the equation 2x â€“ y = 6 and which are not:(i) (3, 0) (ii) (0, 6) (iii) (2, -2) (iv) (âˆš3, 0) (v) (1, -5)       2

Solution:

(i) (3, 0)
Substitute x = 3 and y = 0 in 2x â€“ y = 6
2Ã—3 â€“ 0 = 6
6 = 6 {L.H.S. = R.H.S.}
Therefore, (3,0) is a solution of 2x â€“ y = 6.

(ii) (0, 6)
Substitute
x = 0 and y = 6 in 2x â€“ y = 6
2Ã—0 â€“ 6 = 6
â€“6 = 6 {L.H.S. â‰  R.H.S.}
Therefore, (0, 6) is not a solution of 2x â€“ y = 6.

(iii) (2, -2)
Substitute x = 0 and y = 6 in 2x â€“ y = 6
2Ã—2 â€“ (â€“2) = 6
4 + 2 = 6
6 = 6 {L.H.S. = R.H.S.}
Therefore, (2,-2) is a solution of 2x â€“ y = 6.

(iv) (âˆš3, 0)
Substitute x = âˆš3 and y = 0 in 2x â€“ y = 6
2Ã—âˆš3 â€“ 0 = 6
2 âˆš3 = 6 {L.H.S. â‰  R.H.S.}
Therefore, (âˆš3, 0) is not a solution of 2x â€“ y = 6.

(v) (1/2, -5)
Substitute x =  and y = -5 in 2x â€“ y = 6
2
2 Ã—  â€“ (â€“ 5) = 6
2
1 + 5 = 6
6 = 6 {L.H.S. = R.H.S.}
Therefore, ( 1 , â€“5) is a solution of 2x â€“ y = 6.
2

### Question 4. If x = -1, y = 2 is a solution of the equation 3x + 4y = k, find the value of k.

Solution:

Given,
3 x + 4 y = k
(â€“1, 2) is the solution of 3x + 4y = k.
Substituting x = â€“1 and y = 2 in 3x + 4y = k,
We get,
3Ã—(â€“ 1 ) + 4Ã—2 = k
â€“3 + 8 = k
k = 5
Therefore, k is 5.

### Question 5. Find the value of Î», if x = â€“Î» and y =  5  is a solution of the equation x + 4y â€“ 7 = 0                                                                                                                      2

Solution:

Given,
(-Î»,  5 ) is a solution of equation 3x + 4y = k
2
Substituting x = â€“ Î» and y =  in x + 4y â€“ 7 = 0.
2
We get,
â€“Î» + 4 Ã— 5 â€“ 7 = 0
2
â€“Î» + 10 â€“ 7 = 0
â€“Î» = â€“3
Î» = 3

### Question 6. If x = 2 Î± + 1 and y = Î± â€“ 1 is a solution of the equation 2x â€“ 3y + 5 = 0, find the value of Î±.

Solution:

Given,
(2 Î± + 1, Î± â€“ 1 ) is the solution of equation 2x â€“ 3y + 5 = 0.
Substituting x = 2 Î± + 1 and y = Î± â€“ 1 in 2x â€“ 3y + 5 = 0.
We get,
2Ã—(2 Î± + 1) â€“ 3 Ã— (Î± â€“ 1 ) + 5 = 0
4Î± + 2 â€“ 3Î± + 3 + 5 = 0
Î± + 10 = 0
Î± = â€“10
Therefore, the value of Î± is â€“10.

### Question 7. If x = 1 and y = 6 is a solution of the equation 8x â€“ ay + a2 = 0, find the values of a.

Solution:

Given,
(1 , 6) is a solution of equation 8x â€“ ay + a2 = 0
Substituting x = 1 and y = 6 in 8x â€“ ay + a2 = 0.
We get,
8 Ã— 1 â€“ a Ã— 6 + a2 = 0
a2 â€“ 6a + 8 = 0 (quadratic equation)